THE RELATIONSHIP BETWEEN GYNECOLOGIC CANCER AND REPRODUCTIVE HEALTH AWARENESS AND OBESITY IN WOMEN:A CROSS-SECTION STUDY - Atik, Derya; Kaya Senol, Derya; Unal, Esra; Ağralı, Cansu (Sanamed, 2023)
Purpose: This study was conducted to determine the effect of obesity awareness on gynecological cancer and reproductive health awareness in women.Materials and Methods: This study is a cross-sectıonal study. The sample of the study consisted of overweight and obese women. Data were collected using the introductory information form, obesity awareness scale, and gynecological cancers awareness scale via a Google form. Results: Obesity was found to have a statistically significant association with reproductive health, including the risk for pregnancy and baby, uterus, ovary and breast cancer, menstrual irregularity, age of first menstruation, polycystic ovary syndrome, cesarean section risk, preeclampsia, gestational diabetes, stillbirth risk, birth defects, the chance of conception, the success of fertility treatment, early menopause, osteoporosis, baby weight, and iron deficiency anemia. The total mean score Obesity Awareness Scale and Gynecologic Cancer Awareness Scale was significantly higher among those who believed in this association. A highly significant positive correlation was observed between total and sub-dimension mean scores of women's Obesity Awareness Scale and Gynecologic Awareness Scale.Conclusion: It has been determined that obesity awareness in women is related to reproductive health and gynecological cancer awareness.
Keywords: obesity; Gynecologic cancer; Reproductive health; Awareness